2002
DOI: 10.1016/s0896-6273(01)00557-8
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin and ATP Accelerate Ca2+ Efflux from Rat Sensory Neurons via Protein Kinase C and the Plasma Membrane Ca2+ Pump Isoform 4

Abstract: Modulation of Ca(2+) channels by neurotransmitters provides critical control of neuronal excitability and synaptic strength. Little is known about regulation of the Ca(2+) efflux pathways that counterbalance Ca(2+) influx in neurons. We demonstrate that bradykinin and ATP significantly facilitate removal of action potential-induced Ca(2+) loads by stimulating plasma membrane Ca(2+)-ATPases (PMCAs) in rat sensory neurons. This effect was mimicked in the soma and axonal varicosities by phorbol esters and was blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
123
1
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(144 citation statements)
references
References 47 publications
15
123
1
5
Order By: Relevance
“…This is achieved through subcellular compartmentalization and expression of an appropriate "tool kit" of Ca 2ϩ transporting, buffering, and signaling molecules (19,20). Although the PMCAs are thought to be primarily responsible for the global maintenance of the low resting [Ca 2ϩ ] i , recent data suggest that they participate in local Ca 2ϩ handling and help shape the duration and spreading of subplasmalemmal Ca 2ϩ signals (8,(21)(22)(23)(24). Accordingly, many PMCA isoforms and splice variants are differentially expressed and localized in several tissues and cell types.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved through subcellular compartmentalization and expression of an appropriate "tool kit" of Ca 2ϩ transporting, buffering, and signaling molecules (19,20). Although the PMCAs are thought to be primarily responsible for the global maintenance of the low resting [Ca 2ϩ ] i , recent data suggest that they participate in local Ca 2ϩ handling and help shape the duration and spreading of subplasmalemmal Ca 2ϩ signals (8,(21)(22)(23)(24). Accordingly, many PMCA isoforms and splice variants are differentially expressed and localized in several tissues and cell types.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we examined the hypothesis that PKC activation provides a negative feedback link that is critical for generating the [ PKC can exert negative feedback on phosphoinositide signaling either by phosphorylation and uncoupling of the receptor from Gq (22,23) or by phosphorylation of the ␤ 3 isoform of phospholipase C, which prevents its activation by Gq (24). In addition, PKC can also reduce [Ca 2ϩ ] i by accelerating the rate of Ca 2ϩ extrusion from the cell (25) ] i oscillations, L-phenylalanineinduced oscillations are not controlled by PKC providing negative feedback though the major phosphorylation site at threonine 888 on the CaR. Further experimentation will be necessary to determine the mechanism(s) by which L-phenylalanine induces [Ca 2ϩ ] i oscillations through the CaR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, classic (␣, ␤ 1 , ␤ 2 , and ␥) and/or novel (␦, ⑀, , and ) isoforms of PKC, which are stimulated by [Ca 2ϩ ] i and diacylglycerol or by diacylglycerol, respectively (20,21), can attenuate phosphoinositide signaling either by phosphorylation and uncoupling of the receptor from Gq (22,23) or by phosphorylation of the ␤ 3 isoform of phospholipase C, which prevents its activation by Gq (24). In addition, PKC can also reduce [Ca 2ϩ ] i by accelerating the rate of Ca 2ϩ extrusion from the cell (25). Our recent experiments, using the PKC inhibitor Ro-31-8220, suggested that negative feedback by PKC could also play a role in the generation of [ …”
mentioning
confidence: 99%
“…The slowly developing nature of the increase in PMCA activity would seem to rule out direct activation by Ca 2ϩ -calmodulin. Kinase activation would be a suitable mechanism in that PMCAs can be stimulated by phosphorylation (Penniston and Enyedi 1998;Usachev et al 2002) and Ca 2ϩ -induced autophosphorylation is known to produce sustained kinase activity in neurons (Lisman et al 2002). Whatever the mechanism, it appears that Ca 2ϩ influx via VGCCs is able to stimulate PMCA activity but not Ca 2ϩ influx via NMDA receptors.…”
Section: Stimulus-induced Time-dependent Changes In Pmca Function Arementioning
confidence: 99%
“…These Ca 2ϩ pumps hydrolyze ATP to enable the translocation of Ca 2ϩ up the steep gradient across the plasma membrane (Carafoli and Brini 2000). PMCA diversity results from the alternative splicing of four primary transcripts (Strehler and Zacharias 2001) to produce various pump isoforms differing in their distribution within the brain (Stauffer et al 1995), subcellular localization (DeMarco and Strehler 2001), activity (Enyedi et al 1994), and modulation (Enyedi et al 1996;Usachev et al 2002). Plasma membrane Ca 2ϩ pumps regulate a variety of Ca 2ϩ signaling processes including neurotransmitter release (Empson et al 2007;Zenisek and Matthews 2000) and excitability .…”
Section: Introductionmentioning
confidence: 99%